An overview on emerging bioelectrochemical systems (BESs): Technology for sustainable electricity, waste remediation, resource recovery, chemical production and beyond. (December 2016) - Bajracharya, Suman; Sharma, Mohita; Mohanakrishna, Gunda; Dominguez Benneton, Xochitl; Strik, David P.B.T.B.; Sarma, Priyangshu M.; Pant, Deepak
Abstract: Bioelectrochemical systems (BESs) are unique systems capable of converting chemical energy into electrical energy (and vice-versa) while employing microbes as catalysts. Such organic wastes including low-strength wastewaters and lignocellulosic biomass were converted into electricity with microbial fuel cells (MFCs). Likewise, electrical energy was used to produce hydrogen in microbial electrolysis cells (MECs) or other products including caustic and peroxide. BES were also designed to recover nutrients, metals or removal of recalcitrant compounds. Moreover, photosynthetic micro-organisms as well as higher plants were implemented to use solar energy for electricity generation. The diversity on microbial and enzymatic catalysts offered by nature allows a plurality of potential applications. As compared to conventional fuel cells, BESs operate under relatively mild conditions and do not use expensive precious metals as catalysts. The recently discovered microbial electrosynthesis (MES) of high-value chemicals has greatly expanded the horizon for BES. Newer concepts in application as well as development of alternative materials for electrodes, separators, catalysts along with innovative designs have made BES very promising technology. This article discusses the recent developments that have been made in BESs so far, with the emphasis on their various applications beyond electricity generation and resulting performances as well as existing limitations. Graphical abstract: Highlights: Bioelectrochemical systems (BESs) are emerging rapidly with diverse applications. Bioanode and biocathode performs key processes for energy, fuel or chemicals production. Sustainable microbial electrosynthesis and recovery of energy efficient processes is a recent application. Future perspectives include overcoming limitations for commercialization of BES technology.